Double Regioselective Asymmetric C‐Allylation of Isoxazolinones: Iridium‐Catalyzed N‐Allylation Followed by an Aza‐Cope Rearrangement. Issue 5 (28th December 2017) - Rieckhoff, Stefan; Meisner, Jan; Kästner, Johannes; Frey, Wolfgang; Peters, René
Abstract: Isoxazolinones are biologically and synthetically interesting densely functionalized heterocycles, which for a long time were not accessible in enantioenriched form by asymmetric catalysis. Next to the deficit of enantioselective methods, the functionalization of isoxazolinones is often plagued by regioselectivity issues due to the competition of various nucleophilic centers within the heterocycles. We report the first regio‐ and enantioselective C‐allylations of isoxazolinones. These occur with high regioselectivity in favor of the linear allylation products, although Ir phosphoramidite catalysts were used, which commonly results in branched isomers. Our studies suggest that this outcome is the result of a reaction cascade via an initial regio‐ and enantioselective N‐allylation to provide a branched allyl intermediate, followed by a spontaneous [3, 3]‐rearrangement resulting in chirality transfer. Abstract : Lay it on the line : A regio‐ and enantioselective C‐allylation of isoxazolinones unexpectedly provided linear allylation products, despite the use of iridium phosphoramidite catalysts, which typically provide branched isomers with other nucleophiles. This outcome is explained by a reaction cascade via an initial N‐allylation to provide a branched allyl system, followed by a [3, 3]‐rearrangement step.